Elementary School Students' Perceptions on Independent Curriculum Implementation - Rifda Mardian Arif; Rifda Nur Hikmahwati Arif; Fitrah Sukmadewi M (ARRUS Journal of Social Sciences and Humanities, 2025)
This study aims to determine the perception of elementary school students towards the implementation of the Merdeka Curriculum. This type of research is descriptive with a quantitative approach. This research method uses a survey method. The subjects of the study consisted of 162 student respondents from seven elementary schools, namely SD Laboratorium UNG, SDN 27 South City, SDN 30 South City, Gorontalo City, SDN 50 Dumbo Raya, SDN 11 West City, SDN No. 40 Hulontalangi, Gorontalo, SDN 29 South City District. The data collection technique used a questionnaire technique which was distributed directly to students in these schools. The data analysis technique used descriptive statistics by calculating the percentage of each indicator. The results showed that the indicator with the highest positive response was "The teacher provides real examples of easy-to-understand science material" at 78.15%. The indicator with the lowest percentage was found in the statement "I can choose learning activities in learning according to my wishes," with only 44.82%. The positive response results were 63.89%, neutral responses were 21.12% and negative responses were 15.09%.